Surrogate end points for overall survival in neoadjuvant randomized clinical trials for early breast cancer: original reports : breast cancer - Conforti, Fabio; Nekljudova, Valentina; Sala, Isabella; Ascari, Roberto; Solbach, Christine; Untch, Michael; Denkert, Carsten; Bagnardi, Vincenzo; Pala, Laura; Fasching, Peter A.; Schneeweiss, Andreas; Lück, Hans-Joachim; et al. (Journal of clinical oncology, 2025)
Purpose - To assess trial-level surrogacy value for overall survival (OS) of the pathologic complete response (pCR) and invasive disease-free survival (iDFS) in randomized clinical trials (RCTs) for early breast cancer (BC). - Methods - Individual patient data of neoadjuvant RCTs with available data on pCR, iDFS, and OS were included in the analysis. We used the coefficient of determination R2 from weighted linear regression models to quantify the association between treatment effects on OS and on the surrogate end points. - Results - Eleven RCTs, for a total of 15 treatment comparisons and 12,247 patients, were included in the analysis. There was a weak association between hazard ratios (HRs) for OS and odds ratio of pCR overall (R2, 0.07; 95% CI, 0.00 to 0.48), as well as in all the subgroups explored. Overall, the R2 for the association between HR OS and HR iDFS was 0.46 (95% CI, 0.08 to 0.71), which is just below the cutoff of 0.5 for moderate surrogacy. In the majority of subgroups explored, the R2 ranged from 0.5 to <0.7, while in hormone receptor-/human epidermal growth factor receptor 2- subtype, histologic grade 1-2 tumors, and lobular tumors, surrogacy was strong (ie, R2 ≥0.7). The surrogacy value of iDFS for OS was affected by follow-up (FUP) length: R2 substantially increased up to 36 months of FUP, with little further improvement after 48 months of FUP. - Conclusion - iDFS with sufficient FUP is an acceptable surrogate end point to confidently anticipate final OS results of neoadjuvant RCTs for early BC. This recommendation holds true across many subgroups, with the notable exception of HR+ disease. There is definite need to reassess whether OS is the optimal end point for treatment efficacy measurement in HR+ early BC.